Health secrets hidden in guava leaves: Guava tea, a delicious and natural solution to treat diarrhea in children! - Sundarapandian Vaidyanatahan; Fahmi Sidiq; Nurfadhlina Abdul Halim (International Journal of Research in Community Services, 2023)
This study aims to increase public knowledge about the processing of guava leaves as herbal medicine to treat diarrhea. Prior to counseling and training, the results of the pretest showed that most of the participants (70.5%) had known the utilization and processing of guava leaves as herbal medicine. After attending the training, participants were given a post-test questionnaire to measure the increase in their knowledge.The results showed that there was a significant increase in the participants' knowledge after attending the training. The knowledge percentage increased from 70.5% to 89.0%, representing an increase of 18.5%. This training provides information on how to process guava leaves into herbal medicines that are effective in treating diarrhea.Some of the processing methods taught in the training include making guava leaf tea, guava leaf extract, and decoction of guava leaves. Participants were also given knowledge about the active ingredients in guava leaves, such as quercetin, which has an anti-diarrhea effect.This study showed that the counseling and training program was effective in increasing participants' knowledge about processing guava leaves as a herbal medicine to treat diarrhea. With the knowledge gained, it is hoped that the community can properly process guava leaves and use them effectively in maintaining health and treating diarrhea with simple medication. This program also empowers garden plants in the environment around the village as an easily accessible source of herbal medicines.